Implemantasi Manajemen Kelas Islami Dan Kinerja Guru Dalam Meningkatkan Prestasi Belajar Siswa - Tumiran; Rustam Ependi; Sakban Lubis (Al-Ulum, 2022)
This article mainly focuses on implementing Islamic Classroom Management and Teacher Performance. This study aimed to determine how Islamic classroom management and teacher performance affect student learning achievement. This research uses a quantitative approach with the Ex Post Facto method. The data from the variables are measured using measurement rules and the process of quantifying the rating scale model. The results of the research show that if Islamic classroom management increases. Subsequently, student learning achievement will also increase, and while teacher performance decreases, learning achievement will also decrease. Therefore, the research results on Islamic classroom management are variables, and teacher performance variables have a mutual influence (simultaneously) on student learning achievement.